Potensi Penggunaan Blockchain untuk Meningkatkan Keamanan Jaringan: Telaah Literatur dan Implikasi Masa Depan - Ikhsan, Syaif Nurul; Febriawan, Dimas (TIN: Terapan Informatika Nusantara, 2025)
The digital era has given rise to a high dependency on network infrastructure and data, which simultaneously triggers increasingly complex information security challenges. Cyber attacks such as DDoS, data hacking and information manipulation are real threats. Meanwhile, conventional security solutions are considered not yet fully capable of handling increasingly sophisticated attacks. This research is here to fill the literature gap by exploring the potential of blockchain technology in strengthening network security systems through a systematic literature study approach to 10 recent scientific articles. This research aims to analyze the contribution of blockchain to the main dimensions of security: authentication, integrity, availability and privacy. The methodology used is a qualitative approach based on literature study, with article selection using the criteria of year of publication, theme relevance and academic validity. The results show that blockchain offers significant solutions in terms of immutable transaction recording, decentralized authentication systems, and smart contract-based privacy protection models. These findings reinforce the urgency of integrating blockchain into today's network security architecture, while paving the way for the development of hybrid systems that combine blockchain with AI and IDS.